Analisis Beban Kerja Petugas Information Service di Bandar Udara Internasional Yogyakarta - Wardhana, Pramudika Wisnu; Ubaedillah, Ubaedillah; Rosmayanti, Lina (Sekolah Tinggi Teknologi Kedirgantaraan, 2025)
This study aims to analyze the workload of information service officers at Yogyakarta International Airport (YIA) based on the Manual of Standards (MOS). The research is motivated by the observation that only one officer per shift handles all information-related tasks, which contradicts MOS guidelines requiring a minimum of two officers for airports with fewer than 60 daily flights. The method used is a mixed-method approach combining qualitative and quantitative techniques, including NASA-TLX (Task Load Index) to measure mental workload, along with observations, interviews, and document analysis. Results indicate that the average NASA-TLX score exceeds 80, categorizing the workload as high. The study reveals that excessive multitasking leads to a decline in service quality, increased risk of human error, and potential stress-related issues among personnel. Errors in information dissemination were observed, including incorrect boarding announcements caused by overburdened staff. As a solution, the implementation of a Silent Airport system and better digital information infrastructure is proposed to reduce workload and improve service quality. The study emphasizes the urgency of aligning staffing levels with MOS standards to ensure passenger safety, service efficiency, and institutional compliance.